ISSUES AND PROSPECTS FOR MORTGAGING DEVELOPMENT IN RUSSIAN ECONOMY - Ekaterina Yu. Kalashnikova; Ibragim I. Totorkulov (Вестник Северо-Кавказского федерального университета)
The article focuses on an analysis and evaluation of the mortgage activi-ties, as well as on various related issues; there is also a comparative description provided regarding mortgage offers from various banks; the author also offers calculations towards various interest rates, and gives certain recommendations concerning resolving mortgage issues.